2006
DOI: 10.1016/j.jmaa.2005.07.063
|View full text |Cite
|
Sign up to set email alerts
|

The Jordan–von Neumann constants and fixed points for multivalued nonexpansive mappings

Abstract: The purpose of this paper is to study the existence of fixed points for nonexpansive multivalued mappings in a particular class of Banach spaces. Furthermore, we demonstrate a relationship between the weakly convergent sequence coefficient WCS(X) and the Jordan-von Neumann constant C NJ (X) of a Banach space X. Using this fact, we prove that if C NJ (X) is less than an appropriate positive number, then every multivalued nonexpansive mapping T : E → KC(E) has a fixed point where E is a nonempty weakly compact c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…A more general space than spaces satisfying the Kirk-Massa condition is a space having property (D). Property (D) introduced in [19] 19], Theorem 3.6] Let E be a nonempty weakly compact convex subset of a Banach space X that has property (D). Assume that T : E KC(E) is a nonexpansive mapping.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…A more general space than spaces satisfying the Kirk-Massa condition is a space having property (D). Property (D) introduced in [19] 19], Theorem 3.6] Let E be a nonempty weakly compact convex subset of a Banach space X that has property (D). Assume that T : E KC(E) is a nonexpansive mapping.…”
Section: Preliminariesmentioning
confidence: 99%
“…The class of spaces having property (D) contains several well-known ones including k-uniformly rotund, nearly uniformly convex, uniformly convex in every direction spaces, and spaces satisfying Opial condition (see [3,[19][20][21][22][23] and references therein).…”
Section: Preliminariesmentioning
confidence: 99%
“…It was observed that property D is weaker than the DL condition and stronger than weak normal structure, and Dhompongsa et al 4 proved that property D implies the w-MFPP. Before going to the results, let us recall some more definitions.…”
Section: 6mentioning
confidence: 99%
“…Dhompongsa et al 4 introduced the property D if there exists λ ∈ 0, 1 such that for any nonempty weakly compact convex subset C of X, any sequence {x n } ⊂ C which is regular asymptotically uniform relative to C, and any sequence {y n } ⊂ A C, {x n } which is regular asymptotically uniform relative to X we have r C, y n ≤ λr C, {x n } .…”
Section: 15mentioning
confidence: 99%
“…Dhompongsa et al 3,4 introduced the DL condition and property D which imply the FPP for multivalued nonexpansive mappings. A possible approach to the above problem is to look for geometric conditions in a Banach space X which imply either the DL condition or property D .…”
Section: Introductionmentioning
confidence: 99%